MANAGEMENT OF FINANCIAL AND ECONOMIC PARAMETERS OF AN INNOVATIVE PROJECT WITH CONSIDERATION OF THE REGION SPECIFICS - A. Nikonorova (Вестник университета)
The article is devoted to research of process of financial-economic parameters management of an innovative project. It analyzes the main controlled parameters of projects, proposes to use tools of economic activities analysis in process of management. Efficiency improvement of both new and ongoing projects can be achieved with changing the considered parameters. Conducting of complex analysis of innovative projects is proposed and justified in the article. Parameters based on which it is possible to carry out a complex analysis are considered.